2019
DOI: 10.1074/jbc.ra119.010018
|View full text |Cite
|
Sign up to set email alerts
|

Gα-13 induces CXC motif chemokine ligand 5 expression in prostate cancer cells by transactivating NF-κB

Abstract: Edited by Henrik G. Dohlman GNA13, the ␣ subunit of a heterotrimeric G protein, mediates signaling through G-protein-coupled receptors (GPCRs). GNA13 is up-regulated in many solid tumors, including prostate cancer, where it contributes to tumor initiation, drug resistance, and metastasis. To better understand how GNA13 contributes to tumorigenesis and tumor progression, we compared the entire transcriptome of PC3 prostate cancer cells with those cells in which GNA13 expression had been silenced. This analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…MAZ upregulates Ras expression and then activates NF-κB through the RalGEF/Ral/NF-κB cascade and finally activates the EMT [97,99]. In addition, NF-κB is involved in the heterotrimer G-protein signaling network, which mediates cell adhesion signals through guanine nucleotide-binding protein subunit α-15 (GNA15), and Rho, which promotes CXCL5 expression [100,101]. Another important branch of the Ras-signaling network is the Ras/PI3K/Akt signaling cascade, which transduces signals from growth factor receptors and promotes PCa metastasis, as described in the previous section [102].…”
Section: Ras Signalingmentioning
confidence: 99%
“…MAZ upregulates Ras expression and then activates NF-κB through the RalGEF/Ral/NF-κB cascade and finally activates the EMT [97,99]. In addition, NF-κB is involved in the heterotrimer G-protein signaling network, which mediates cell adhesion signals through guanine nucleotide-binding protein subunit α-15 (GNA15), and Rho, which promotes CXCL5 expression [100,101]. Another important branch of the Ras-signaling network is the Ras/PI3K/Akt signaling cascade, which transduces signals from growth factor receptors and promotes PCa metastasis, as described in the previous section [102].…”
Section: Ras Signalingmentioning
confidence: 99%
“…2G). Importantly, the p65 NF-κB binding elements of each of these genes has been fully annotated and all lie within 100bp of the TSS (2932). Notably, we did not observe differences in histone acetylation at the HDAC3-bound genomic regions associated with upregulated gene expression (Fig.…”
Section: Hdac3 Represses the P65 Nf-κb Sasp Transcriptional Programmentioning
confidence: 99%
“…The enzymatic activity of HDAC3 is dependent on its interaction with NCoR or SMRT. Nuclear receptors function as signal-dependent transcription factors that integrate and deliver developmental, hormonal, environmental and nutrient cues to the genome, thereby acting as genetic switches of gene transcription [32][33][34][35] . In the classical model of nuclear receptor function, ligand binding elicits an allosteric change in the structure of the nuclear receptor, which facilitates differential recruitment of co-activators or co-repressors 36,37 Co-activators with HAT activity bind to ligand-bound nuclear receptors, whereas co-repressors bind ligand-free nuclear receptors to directly mediate gene repression or less commonly to indirectly mediate gene activation (FIG.…”
mentioning
confidence: 99%
“…Mounting evidence suggests that the NF-κB signaling pathway is involved in the progression of various human tumors, including those of ovarian cancer (43), prostate cancer (44), cervical cancer (45), as well as head and neck cancer (46). A recent study demonstrated that TRIM22 negatively regulates the tumor necrosis factor receptor-associated factor 6 (TRAF6)-stimulated NF-κB pathway by binding to the TRIM22 N-terminal RING domain (47).…”
Section: Discussionmentioning
confidence: 99%